Production of bacterial cellulose from alternative low-cost substrates (2017)
Cellulose is the most widely used biopolymer on Earth. Its large-scale production is mainly from lignocellulosic material (plant origin), however, this plant material is not the only source of this valuable polymer, since microorganisms, like bacteria, naturally produce cellulose, especially those of the genus Komagateibacter (formerly Gluconacetobacter). This type of cellulose is of great interest because of its unique properties such as high purity and resistance, nevertheless, it has not been produced in a large-scale industrial process to date using low-cost substrates, one of the key aspects that should be considered for the industrial obtaining of any biotechnological product. As a main finding we found that the majority of low-cost culture media discussed could have the potential to produce bacterial cellulose on an industrial scale, since in most cases they yield more cellulose (with similar physical chemical characteristics) to those obtained in standard media. However, for an appropriate large-scale production, a specific knowledge about these by-products (since their composition and characteristics, which have a direct impact on the productivity of this biopolymer, are quite heterogeneous) and a proper standardization of them would also be required. Research staff of many industries could use the information presented here to help design a process to use their respective byproducts as substrate to obtain a product with a high added value as bacterial cellulose.